An Introduction to Merchandise–Part IV: Italian Book-keeping/ Part V: Practical Book-keeping (Book). - Hendrickson, Harvey S. (The Accounting Review, 1985)
Reviews the book "An Introduction to Merchandise," part IV, "Italian Book-keeping," and part V "Practical Book-keeping," by Robert Hamilton.